2D Dual-Metal Zeolitic-Imidazolate-Framework-(ZIF)-Derived Bifunctional Air Electrodes with Ultrahigh Electrochemical Properties for Rechargeable Zinc-Air Batteries; Advanced Functional Materials; Vol. 28, iss. 5 - Wang Tingting; Kou Zongkui; Shichun Mu; Jingping Liu; Daping He; Amiinu I. S. Ibrahim Saana; Wen Meng; Kui Zhou; Zhixiong Luo; Chaemchuen S. Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen